Phase I study of the anti-CD74 monoclonal antibody milatuzumab (hLL1) in patients with previously treated B-cell lymphomas. Issue 11 (2nd November 2015) - Martin, Peter; Furman, Richard R.; Rutherford, Sarah; Ruan, Jia; Ely, Scott; Greenberg, June; Coleman, Morton; Goldsmith, Stanley J.; Leonard, John P.
Abstract : Milatuzumab (hLL1), a humanized anti-CD74 monoclonal antibody, has activity in preclinical non-Hodgkin lymphoma (NHL) models. We conducted a phase 1 trial in previously treated B-cell malignancies. Dose escalation included four planned dose levels (1.5, 4, 6 and 8 mg/kg) with milatuzumab given twice weekly for 6 weeks. After dose level 1, the schedule was changed to daily (Monday–Friday) for 10 days. Twenty-two patients were treated. The most common possibly related toxicities were infusion reaction, anemia, lymphopenia, neutropenia and thrombocytopenia. Three patients experienced dose-limiting toxicity (neutropenia, neutropenia, rash) at dose levels 1, 2 and 4, respectively. Eight patients had stable disease, with no objective responses. The serum half-life of milatuzumab was ∼2 h. In seven patients, In-111 imaging showed no clear evidence of tumor targeting. The short half-life may reflect CD74 rapid internalization and presence on extratumoral tissues; this antigen sink must be overcome to capitalize on the promising preclinical activity of the drug.